Relationship of Nutritional Status with Tuberculosis Lungs of Children Aged 0-5 Years in Surabaya - Manillaturrochmah Manillaturrochmah; Widati Fatmaningrum; Retno Asih Setyoningrum; Budi Utomo (Pelopor Publikasi Akademika, 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis. TB is the number 10 cause of death in the world. Indonesia is the third TB contributor in the world after India and China. TB in children is the leading cause of morbidity and mortality worldwide. The increase in TB is influenced by endurance, low nutritional status, lack of individual, hygiene, and shelter density. Objective of this research analyzed the relationship between nutritional status and the incidence of pulmonary TB at Dr. Soetomo Hospital Surabaya. The research design is a retrospective analytical observational research with a case-control study design, with a sampling technique using probability sampling, namely purposive sampling. The analysis uses the coefficient contingency Lambda statistical test and has been approved by the ethics committee of Dr. Soetomo Hospital Surabaya. A total sample of 130 patients was studied, and the analysis results showed an association between nutritional status and TB incidence (p = 0.019). After finalization by healthy status category, there was no association between overweight nutritional status (p=0.259) and obesity nutritional status (p=0.513). Conclusion: There is a link between nutritional status and TB incidence, but after finalization based on healthy status categories. There is no relationship between overweight and obese dietary status and the incidence of tuberculosis.